Revolusi Belajar Matematika: Eksplorasi Pengaruh Media Digital Interaktif terhadap Hasil Belajar Siswa di Sekolah Menengah Pertama - Santika, Lisa; Wahidin; Supriadi, Edi (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study evaluates the impact of integrated multi-platform interactive digital media on students' mathematics learning outcomes to address the limitations of conventional teaching methods in the digital era.Design/methodology/approach: A quantitative quasi-experimental design was employed, categorizing subjects into experimental and control groups. The intervention integrated various interactive digital platforms specifically for the Relations and Functions topic, with academic achievement data collected through validated post-test instruments.Findings: Statistical analysis confirms a positive and significant effect of digital media usage. However, the calculated effect size remains low, particularly regarding abstract topics. This finding indicates that technological effectiveness varies significantly based on the characteristics of the instructional content.Practical implications: Educators are advised to be more selective in integrating technology, ensuring additional pedagogical support for abstract concepts that may not be fully resolved through digital visualization alone.Originality/value: The novelty of this study lies in its holistic examination of multiple digital platforms as a single intervention model and the identification of empirical boundaries of interactive media efficacy on specific mathematical content.     Purpose: Penelitian ini bertujuan mengevaluasi pengaruh integrasi multi-platform media digital interaktif terhadap hasil belajar matematika siswa untuk mengatasi keterbatasan metode konvensional di era digital. Design/methodology/approach: Menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimen. Subjek penelitian terbagi menjadi kelompok eksperimen dan kontrol. Intervensi melibatkan sinergi berbagai platform digital interaktif pada materi Relasi dan Fungsi, dengan data capaian akademik yang diukur melalui instrumen tes akhir yang telah divalidasi ahli.Findings: Hasil analisis statistik membuktikan adanya pengaruh positif dan signifikan dari penggunaan media digital. Namun, ukuran efek yang dihasilkan tergolong rendah, terutama pada materi yang bersifat abstrak. Temuan ini mengindikasikan bahwa efektivitas teknologi bervariasi tergantung pada karakteristik materi ajar.Practical implications: Pendidik disarankan untuk lebih selektif dalam mengintegrasikan teknologi, dengan memberikan penguatan pedagogis tambahan pada konsep-konsep abstrak yang tidak cukup hanya dibantu oleh visualisasi digital.Originality/value: Kebaruan studi ini terletak pada pengujian holistik berbagai jenis platform digital sebagai satu kesatuan intervensi, serta identifikasi batasan empiris media interaktif terhadap materi matematika tertentu.